اثر تقلبات أسعار النفط الخام في الطلب على مصادر الطاقة البديلة للمدة (1973-2008) - HASSAN, KHALIL G.; SAID, KHABBAT ABDULKAREEM (Journal of Duhok University, 2020)
ABSTRACT Crude oil is one of the most important and depleted resources used as an energy source for decades. While high oil prices have slowed global economic activity, they are a major cause of the shift towards alternative energy sources. This study is an attempt to answer the question of whether fluctuations in crude oil prices will shift to alternative sources and thus reduce the relative importance of crude oil in the global energy balance. In favor of alternative energy sources, alternative energy demand models have been estimated at several levels, including individual countries such as China and India, a group of countries such as the European Union, the North American group and, finally, the overall level of the world. To achieve the objectives of the research and test its hypothesis, the parameters to be estimated according to the methodology of econometrics were analyzed. Perhaps the most important conclusion is the significant impact of fluctuations in crude oil prices on the demand for alternative sources of crude oil for energy purposes.